2019
DOI: 10.1155/2019/9827574
|View full text |Cite
|
Sign up to set email alerts
|

miR-98 Modulates Cytokine Production from Human PBMCs in Systemic Lupus Erythematosus by Targeting IL-6 mRNA

Abstract: Objective There is evidence that interleukin-6 (IL-6) upregulation plays a critical role in immunopathology of systemic lupus erythematosus (SLE). MicroRNA- (miRNA-) 98 was predicted to bind with the 3′-untranslated region (3′-UTR) of IL-6 gene. We hypothesized miR-98 through its regulation of IL-6 gene expression to influence cytokine production from peripheral blood mononuclear cells (PBMCs) in SLE. Methods The expression of miR-98 and IL-6 mRNA in the PBMCs of 41 SLE patients and 20 healthy controls (HC) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The results of a study on the peripheral blood mononuclear cells (PBMCs) samples of systemic lupus erythematosus (SLE) patients showed that miR-98-5p directly targeted IL-6 and inhibited the production of inflammatory cytokines and cell proliferation through IL-6/STAT3 pathway [97] . Moreover, the results of a dual luciferase reporter assay in human adipose stem cells indicated that miR-223-3p regulated the expression of inflammatory cytokines IL-6 and STAT3 (J.…”
Section: The Role Of Mirnas In Regulating Jak-stat Signaling Pathwaymentioning
confidence: 99%
“…The results of a study on the peripheral blood mononuclear cells (PBMCs) samples of systemic lupus erythematosus (SLE) patients showed that miR-98-5p directly targeted IL-6 and inhibited the production of inflammatory cytokines and cell proliferation through IL-6/STAT3 pathway [97] . Moreover, the results of a dual luciferase reporter assay in human adipose stem cells indicated that miR-223-3p regulated the expression of inflammatory cytokines IL-6 and STAT3 (J.…”
Section: The Role Of Mirnas In Regulating Jak-stat Signaling Pathwaymentioning
confidence: 99%
“…This summary of the current research results has shown that various, ubiquitous and functional miRNAs are involved in most immunological events leading to SLE. The upregulation of let-7c contributes to proinflammatory features of DCs in SLE ( 23 ); MiR-7 is associated with the overactivation of B cells and subsequent autoantibody production ( 37 ); MiR-21 up-regulation contributes to T cell hyperactivity ( 51 ); MiR-34a is associated with defection of Tregs and immune tolerance breakdown ( 65 ); Transfection of miR-98 alleviates the increased production of inflammatory cytokines ( 96 ). Different miRNAs can target the same mRNA, and one miRNA can target multiple mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-98 modulates STAT3 phosphorylation through the regulation of IL-6 expression. Thus, miR-98 can amend STAT3-associated cell proliferation and the release of pro-inflammatory cytokines in patients with SLE [ 40 ]. The downregulation of miR-98 has also been reported in SLE CD4+ T cells, while Fas levels were enhanced [ 41 ].…”
Section: Mirnas In Slementioning
confidence: 99%